Molecular and agro-morphological diversity assessment of some bread wheat genotypes and their crosses for drought tolerance - Ezzat, Mohamed A.; Alotaibi, Nahaa M.; Soliman, Said S.; Sultan, Mahasin; Kamara, Mohamed M.; Abd El-Moneim, Diaa; Felemban, Wessam F.; Al Aboud, Nora M.; Aljabri, Maha; Abdelmalek, Imen Ben; Mansour, Elsayed; Hassanin, Abdallah A. (PeerJ, 2024)
Wheat, a staple cereal crop, faces challenges due to climate change and increasing global population. Maintaining genetic diversity is vital for developing drought-tolerant cultivars. This study evaluated the genetic diversity and drought response of five wheat cultivars and their corresponding F1 hybrids under well-watered and drought stress conditions. Molecular profiling using ISSR and SCoT-PCR markers revealed 28 polymorphic loci out of 76 amplified. A statistically significant impact of parental genotypes and their crosses was observed on all investigated agro-morphological traits, including root length, root weight, shoot length, shoot weight, proline content, spikelet number/spike, spike length, grain number/spike, and grain weight/spike. The parental genotypes P1 and P3 had desirable positive and significant general combining ability (GCA) effects for shoot fresh weight, shoot dry weight, root fresh weight, root dry weight, shoot length, and root length under well-watered conditions, while P3 and P5 recorded the highest GCA estimates under drought stress. P3 and P4 showed the highest GCA effects for number of spikelets per spike, the number of grains per spike, and grain weight per spike under normal conditions. P5 presented the maximum GCA effects and proved to be the best combiner under drought stress conditions. The cross P1× P3 showed the highest positive specific combining ability (SCA) effects for shoot fresh weight under normal conditions, while P2×P3 excelled under water deficit conditions. P1× P2, P1 × P3, and P4× P5 were most effective for shoot dry weight under normal conditions, whereas P1×P3 and P3×P5 showed significant SCA effects under drought stress. Positive SCA effects for root fresh weight and shoot length were observed for P3×P5 under stressed conditions. Additionally, P4×P5 consistently recorded the highest SCA for root length in both environments, and P3×P5 excelled in the number of spikelets, grains per spike, and grain weight per spike under drought conditions. The evaluated genotypes were categorized based on their agronomic performance under drought stress into distinct groups ranging from drought-tolerant genotypes (group A) to drought-sensitive ones (group C). The genotypes P5, P2×P5, and P3×P5 were identified as promising genotypes to improve agronomic performance under water deficit conditions. The results demonstrated genetic variations for drought tolerance and highlighted the potential of ISSR and SCoT markers in wheat breeding programs for developing drought-tolerant cultivars.
Keywords: Abiotic stress; Cereal crops; Drought; ISSR markers; Molecular diversity; SCoT markers